2019
DOI: 10.1177/0300060519847866
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio predicts hematoma growth in intracerebral hemorrhage

Abstract: Objective Early hematoma growth is a major determinant of early neurological deterioration and poor clinical outcome in patients with spontaneous intracerebral hemorrhage (ICH). Inflammation plays a major role in the pathophysiology of ICH. This study aimed to evaluate the potential of the neutrophil-to-lymphocyte ratio (NLR) for predicting early hematoma growth after ICH. Methods A retrospective review was performed of patients with acute spontaneous ICH who were admitted to the Stroke Center of the First Peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…[23][24][25][26][27] Recently, accumulating evidence supports that higher PMNs count and neutrophil to lymphocyte ratio (NLR) at early stage of ICH leads to the poorer outcome. [4][5][6][7] Thus, in a proof-of-concept experiment in rat model of ICH, we found that simvastatin effectively decreased the peripheral PMNs count, NLR and neutrophil brain-invading, as well as attenuated brain edema and neurological de cits following ICH.…”
Section: Simvastatin Exerted Pro-apoptotic Effect On Pmns In Acute Stage After Ich Via Lxa4/fpr2/p38 Mapk Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Recently, accumulating evidence supports that higher PMNs count and neutrophil to lymphocyte ratio (NLR) at early stage of ICH leads to the poorer outcome. [4][5][6][7] Thus, in a proof-of-concept experiment in rat model of ICH, we found that simvastatin effectively decreased the peripheral PMNs count, NLR and neutrophil brain-invading, as well as attenuated brain edema and neurological de cits following ICH.…”
Section: Simvastatin Exerted Pro-apoptotic Effect On Pmns In Acute Stage After Ich Via Lxa4/fpr2/p38 Mapk Signaling Pathwaymentioning
confidence: 99%
“…Recently, clinical reports indicate that early peripheral blood polymorph nuclear neutrophils (PMNs) elevation is closely related to the poor prognosis of patients with ICH, which is often accompanied by heavier brain edema and larger hematoma. [4][5][6][7] To understand the relationship between the elevated PMNs and poor prognosis among ICH patients, we performed a con rmatory experiment in a rat model of ICH. [8] The results show that the ICH rat showed a signi cant increase of PMNs in peripheral blood at an early stage, which is consistent with the clinical phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in this study we found a significant increase of microglia after ICH in mice and microglia activation peaked at 24 h after injury. Neutrophil-lymphocytes ratio (NLR) has been extensively reported as a risk factor associated with bad outcomes after ICH [23,33] Post-stroke immunological response has been extensively studied, especially in ischemia stroke [19].…”
Section: Secondary Brain Injury Such As Blood-brain Barrier (Bbb) DImentioning
confidence: 99%
“…After ischemic stroke, spleen was activated and the brainspleen cell cycling started. It is still controversial what plays the key role in the splenic response after stroke, the lymphocytes, monocytes, [22] neutrophil infiltration or the neutrophil-to-lymphocyte ratio (NLR) [23]. Moreover, it is worthwhile to elucidate the precise role of each cell type of spleen in secondary brain injury after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Liu et al (2019) reported that a higher NLR level was significantly correlated with major disability at 90 days and a higher short-term mortality rate. Wang Z. et al (2019) suggested that NLR can predict hematoma expansion. Finally, Lattanzi et al (2017) indicated that NLR may be a prognostic factor for neurological deterioration.…”
Section: Introductionmentioning
confidence: 99%